2011
DOI: 10.5993/ajhb.35.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Exercising with an iPod, Friend, or Neither: Which is Better for Psychological Benefits?

Abstract: To examine the role of music and social contact on exercise benefits. Methods: Two hundred twenty-nine (n=229) students were randomly assigned to one of 6 conditions: biking alone with iPod or friend in a laboratory, walking alone with iPod or friend outdoors, or biking or walking alone in control conditions. All participants completed 20 minutes of exercise at 70% of their maximum target heart rate. Results: Exercising in control conditions indoors resulted in a more relaxed and calm response. Exercising outd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…It may be worthwhile to note that enjoyment in most prior studies was measured when exercising with a friend, while the current study involved exercising with a stranger. Despite contradictory findings regarding enjoyment, past research has indicated that participants felt the most calm when exercising alone than with a partner (12,13). These findings, as well as those of the current study, suggest that individuals may feel more at ease when there are no immediate social standards for comparison.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…It may be worthwhile to note that enjoyment in most prior studies was measured when exercising with a friend, while the current study involved exercising with a stranger. Despite contradictory findings regarding enjoyment, past research has indicated that participants felt the most calm when exercising alone than with a partner (12,13). These findings, as well as those of the current study, suggest that individuals may feel more at ease when there are no immediate social standards for comparison.…”
Section: Discussioncontrasting
confidence: 46%
“…This suggests that when comparing themselves to an unattractive female, participants may feel less threatened than when comparing themselves to an attractive female. Previous research have not found differences in tension when exercising alone versus with a partner (11)(12)(13), however one study has found that female pairs reported greater exertion than mixed pairs while exercising (10). This suggests that perhaps people feel more distracted or less competitive in mixed pairs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that music and exercise may combine to increase energy and positive mood significantly more than exercise alone. With regard to exercise enjoyment, participants who listened to music during exercise rated their exercise as more enjoyable than those who exercised without music, and this effect size was medium (d = .33 Campbell and White | Music and Exercise enjoyment has been indicated in previous research using high-intensity exercise (Miller et al, 2010), but this effect has not been previously supported for low-to moderate-intensity exercise (Plante et al, 2011).…”
Section: Discussionmentioning
confidence: 85%
“…With regard to exercise enjoyment, participants who listened to music during exercise rated their exercise as more enjoyable than those who exercised without music, and this effect size was medium (d = .33). The positive effect of music on Campbell and White | Music and Exercise enjoyment has been indicated in previous research using high-intensity exercise (Miller et al, 2010), but this effect has not been previously supported for low-to moderate-intensity exercise (Plante et al, 2011).…”
Section: Discussionmentioning
confidence: 90%